Global research hotspots and trends in microglia in ischemic stroke - Liu, Yingquan; Ye, Yu; Dai, Fan; Bai, Lin; Ji, Hongjie; Su, Xingxing; Hu, Peijia; Cheng, Hongliang (Frontiers in Immunology, 2025)
ObjectiveThis study explores potential therapeutic strategies by analyzing the bibliometric analysis of microglia in ischemic stroke (IS) to identify the current status, hotspots, and trends in research.MethodsIn this study, we visualized publications on IS and microglia indexed in the Web of Science Core Collection between January 1, 2010, and March 15, 2025, using VOSviewer and CiteSpace software. In addition, we optimized several visualization maps using Pajek and Scimago Graphica to present the analysis results more clearly and intuitively.ResultsA total of 2,117 articles and reviews from 465 journals were included in the analysis. The number of publications reveals a steady increase over the years. China and the United States lead the field in terms of influence. Jun Chen from the University of Pittsburgh is the most influential scholar, and the Journal of Neuroinflammation is the most frequently cited journal among researchers. Through visual analysis of subject categories, keywords, and references, we found neuroinflammation to be the central mechanism in this research area. Therapeutic approaches primarily focus on using mesenchymal stem cells and extracellular vesicles, representing one of the most promising translational strategies for treating IS. Furthermore, innovative applications of neuroimaging technology and nanotechnology are facilitating the translation of basic research into clinical practice.ConclusionThis study uses bibliometric methods to summarize key findings in microglia-related IS research. The insights gained will provide valuable guidance and reference for developing new immunotherapeutic strategies based on microglia for more effective prevention and treatment of IS.